A Cyclin Dependent Kinase Regulatory Subunit (CKS) Gene of Pigeonpea Imparts Abiotic Stress Tolerance and Regulates Plant Growth and Development in Arabidopsis - Tamirisa, Srinath; Vudem, Dashavantha R.; Khareedu, Venkateswara R. (Frontiers in Plant Science, 2017)
Frequent climatic changes in conjunction with other extreme environmental factors are known to affect growth, development and productivity of diverse crop plants. Pigeonpea, a major grain legume of the semiarid tropics, endowed with an excellent deep-root system, is known as one of the important drought tolerant crop plants. Cyclin dependent kinases (CDKs) are core cell cycle regulators and play important role in different aspects of plant growth and development. The cyclin-dependent kinase regulatory subunit gene (CKS) was isolated from the cDNA library of pigeonpea plants subjected to drought stress. Pigeonpea CKS (CcCKS) gene expression was detected in both the root and leaf tissues of pigeonpea and was upregulated by polyethylene glycol (PEG), mannitol, NaCl and abscisic acid (ABA) treatments. The overexpression of CcCKS gene in Arabidopsis significantly enhanced tolerance of transgenics to drought and salt stresses as evidenced by different physiological parameters. Under stress conditions, transgenics showed higher biomass, decreased rate of water loss, decreased MDA levels, higher free proline contents and glutathione levels. Moreover, under stress conditions transgenics exhibited lower stomatal conductance, lower transpiration and higher photosynthetic rates. However, under normal conditions, CcCKS-transgenics displayed decreased plant growth rate, increased cell size and decreased stomatal number compared to those of wild-type plants. Real-time polymerase chain reaction revealed that CcCKS could regulate the expression of both ABA-dependent and ABA-independent genes associated with abiotic stress tolerance as well as plant growth and development. As such, the CcCKS seems promising and might serve as a potential candidate gene for enhancing the abiotic stress tolerance of crop plants.